Use of pirfenidone in fibrotic interstitial lung diseases and beyond: a review - Han, Mingfeng; Liu, Qijia; Ji, Zhe; Jin, Lili; Jin, Wenyu; Gao, Zhonggao (Frontiers in Medicine, 2024)
The pathophysiological mechanisms involved in fibrotic interstitial lung diseases (FILDs) are akin to those observed in idiopathic pulmonary fibrosis (IPF), implying the potential for shared therapeutic approaches. Pirfenidone exhibits antifibrotic and anti-inflammatory properties, making it the first small-molecule drug approved for treating IPF. Pirfenidone has been utilized in IPF treatment for more than one decade. However, guidelines for progressive pulmonary fibrosis (PPF) treatment suggest that further research and evidence are needed to fully comprehend its efficacy and safety across various PPF subtypes. In recent years, numerous studies have explored the use of pirfenidone in treating non-IPF FILD. Herein, we provide an overview of the latest research data on application of pirfenidone in occupational-related ILD, connective tissue disease-associated ILD, postcoronavirus disease-2019 pulmonary fibrosis, and other conditions. We summarize the level of evidence and highlight challenges associated with using pirfenidone in different FILDs to offer clinical guidance.